2021
DOI: 10.1109/access.2021.3096062
|View full text |Cite
|
Sign up to set email alerts
|

On the Security of IIoT Deployments: An Investigation of Secure Provisioning Solutions for OPC UA

Abstract: A key technology for the communication in the Industrial Internet of Things (IIoT) is the Open Platform Communications Unified Architecture (OPC UA). OPC UA is a standard that enables interoperable, secure, and reliable communication between industrial devices. To defend against cyber attacks, OPC UA has built-in security mechanisms that protect the authenticity, integrity, and confidentiality of data in transit. Before communicating securely, it is essential that OPC UA devices are set up in a secure manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Likewise, the owner of the IoT platforms will allocate an account in the IoT servers to deploy the CMXsafe agent [19]. The orchestrator location depends on the specifics of each IoT deployment [20]. Business-critical environments can be located on the local site, whereas in distributed IoT environments, the orchestrator can be deployed as a cloud service.…”
Section: B Cmxsafe Configuration and Operationmentioning
confidence: 99%
“…Likewise, the owner of the IoT platforms will allocate an account in the IoT servers to deploy the CMXsafe agent [19]. The orchestrator location depends on the specifics of each IoT deployment [20]. Business-critical environments can be located on the local site, whereas in distributed IoT environments, the orchestrator can be deployed as a cloud service.…”
Section: B Cmxsafe Configuration and Operationmentioning
confidence: 99%
“…Runde et al [34], Hausmann et al [30], Fischer et al [28], Danilchenko et al [45], Höglund et al [46], Astorga et al [11], and Kohnhäuser et al [51] propose mechanisms for the secure onboarding and initial equipment of devices with certificates issued by the domain of the owner or operator. These mechanisms are secured by using credentials installed on an IA component at manufacturing time.…”
Section: Approaches Presented In Research Papersmentioning
confidence: 99%
“…These mechanisms are secured by using credentials installed on an IA component at manufacturing time. Runde et al [34] contribute a comprehensive protocol proposal for PROFINET, and Kohnhäuser et al [51] refer their elaborations to OPC UA.…”
Section: Approaches Presented In Research Papersmentioning
confidence: 99%
“…Internet-wide Industrial Security Assessments: While the security of deployments in other areas is often widely assessed, the configuration of industrial deployments relying on security features was rarely covered by research. Focusing on the secureby-design OPC UA protocol, related work showed that operators frequently fail to configure deployments securely [17], possibly due to constrained protocol implementations [26], and presented mechanisms for a more secure device provisioning [54].…”
Section: Related Workmentioning
confidence: 99%